Pemanfaatan Kascing Berbasis Kearifan Lokal untuk Meningkatkan Kualitas Pupuk Organik - Maroeto Maroeto; Rossyda Priyadarshini; Dewi Puspa Arum; Agung Winarno; Ken Bening Jiwa Jeni (GUYUB: Journal of Community Engagement, 2025)
This community service program was implemented at the Sabilus Salam Sharia Cooperative, Notorejo Hamlet, Wonosalam District, Jombang Regency, East Java. It involved 25 farmers and 10 cooperative members, and was facilitated by a service team consisting of four lecturers and one master’s (S2) student. The uniqueness of this program lies in the utilization of kascing (earthworm castings) based on the local wisdom of Wonosalam, integrated with the use of local organic waste and the strengthening of cooperative institutions through a Participatory Action Research (PAR) approach. This distinguishes the program from conventional organic fertilizer training, which is typically one-directional. The objective of the activity was to enhance farmers’ capacity to produce and apply both liquid and solid organic fertilizers based on kascing, in order to reduce dependence on chemical fertilizers and improve soil quality. The methods employed included socialization, participatory training, field assistance, and experimental demonstration plots. Standardized laboratory test results indicated an increase in soil pH from 3.25 to 5.42, organic carbon (C-organic) from 0.23% to 0.53%, as well as improvements in the levels of nitrogen, phosphorus, and potassium. Post-training evaluation showed that 84% of participants understood the stages of kascing fertilizer production, and 72% had applied it on their respective farms. Overall, the program proved effective in measurably improving soil quality and strengthening the independence of farmers and the cooperative in developing sustainable agriculture based on local resources..